(3OdGFd GdYHGO aj TQM GdEQTGOs - (3GdfhQj, GdWHQSj, eMeO Jbj Hf Ydj eMeO Hf Jbj, J(B1263(3g`s ((3eMeO MSf Hf TYHGf Hf Ydjs)
(3ChdgG (B:s
...(3cJGH GdeJGLQ hajg ebGUO GdChd aj GdebOeGJ hajg eWdHGf GdChd aj CbSGegG(B...s
(3BNQgG (B:s
...(3aEf GfJaJ aGdbhd bhd GdhGSWI eY Gdjejf hdG fRGY aj TjA ef gPg GdCMcGe(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B181s
(3GdPQjYI(B:(3L(B8(3,U(B177(3,Qbe(B1034s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis